Latihan “Kombo Yoga Romla” (Kombinasi Yoga Dan Aromaterapi Lavender) Sebagai Upaya Pendampingan Aktivitas Fisik Ibu Hamil Dalam Meningkatkan Kualitas Tidur Pada Ibu Hamil - Shinta Wurdiana Rhomadona (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2021)
One of the main factors that affect the quality of sleep are different periods of life such as pregnancy. Insomnia is a sleep quality disorder that is often experienced during pregnancy. In addition, pregnant women can experience insomnia throughout pregnancy depending on the proportion of body shape and increase in stomach size. Psychological changes such as anxiety before birth, concentration on changing relationships with partners, and anxiety over financial problems also contribute to worsening sleep quality in pregnant women. Adverse clinical outcomes include an increased risk of gestational hypertensive disorders, glucose intolerance, preterm labor, and postpartum depression. Sleep disorders can also cause depression and stress that affect the fetus. Efforts to overcome sleep difficulties include yoga and aromatherapy. Physiologically, this yoga exercise will reverse the effects of stress involving the parasympathetic part of the central nervous system which has an effect on decreasing heart rate, breathing rhythm, blood pressure, muscle tension, metabolic rate, and the production of stress hormones. Thus, pregnant women will feel relaxed as the quality of sleep for pregnant women improves. Apart from yoga, aromatherapy has been widely used to elevate mood and relax the body. The scent of lavender induces the mind to improve the quality of one's sleep and can provide a mild sedative effect. Community service this time focuses on pregnant women, especially pregnant women in the third trimester, related to the need to treat sleep disturbances because if not corrected it can cause problems in the health of the mother and fetus. Midwife Independent Practice (PMB) Lita Anggraeni, Amd.keb, with the address Jl. Mountain. Anyar Jaya I/4, District. Mountain. Anyar, Surabaya is a place for basic health services that provides services to patients (individuals, families and communities) who have a significant contribution in providing health services, especially in comprehensively improving the welfare of mothers and children. This time for community service, the team and partners have agreed to do the "Kombo Yoga Romla" exercise, which is a combination of yoga and lavender aromatherapy as an effort to assist pregnant women with physical activity in improving sleep quality in pregnant women. The application of these two methods is expected to reduce sleep problems in these pregnant women.